2018
DOI: 10.3389/fneur.2018.00581
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrastructural Characteristics of Neuronal Death and White Matter Injury in Mouse Brain Tissues After Intracerebral Hemorrhage: Coexistence of Ferroptosis, Autophagy, and Necrosis

Abstract: Although intracerebral hemorrhage (ICH) is a devastating disease worldwide, the pathologic changes in ultrastructure during the acute and chronic phases of ICH are poorly described. In this study, transmission electron microscopy was used to examine the ultrastructure of ICH-induced pathology. ICH was induced in mice by an intrastriatal injection of collagenase. Pathologic changes were observed in the acute (3 days), subacute (6 days), and chronic (28 days) phases. Compared with sham animals, we observed vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
100
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 63 publications
5
100
0
2
Order By: Relevance
“…Zille et al (2017) also confirmed that ferroptosis and necroptosis were the main features of experimental hemorrhagic stroke in vitro and in vivo and suggested that the ferroptosis inhibitor deferoxamine may elicit significant functional recovery in some models and clinical patients of ICH. Li et al (2018) also observed the ultrastructure of ICH-induced pathology through transmission electron microscopy, including in cells undergoing ferroptosis, necroptosis, and autophagy.…”
Section: Intracerebral Hemorrhage and Ferroptosismentioning
confidence: 98%
“…Zille et al (2017) also confirmed that ferroptosis and necroptosis were the main features of experimental hemorrhagic stroke in vitro and in vivo and suggested that the ferroptosis inhibitor deferoxamine may elicit significant functional recovery in some models and clinical patients of ICH. Li et al (2018) also observed the ultrastructure of ICH-induced pathology through transmission electron microscopy, including in cells undergoing ferroptosis, necroptosis, and autophagy.…”
Section: Intracerebral Hemorrhage and Ferroptosismentioning
confidence: 98%
“…Morphologically, the mitochondria of ferroptotic neurons appeared shrunken, with decreased cytomembrane mitochondria at 3 and 6 days after ICH in mice. After several days, the swollen mitochondrial count appears to stabilize and is sustained until 28 days (Li et al, 2018). Interestingly, another study failed to find the shrunken mitochondria in primary neurons subjected to hemin stimulation (Zille et al, 2017).…”
Section: Ferroptosis In Hemorrhagic Strokementioning
confidence: 99%
“…Fragmentation and degeneration of organelles exposes more proteins or polypeptides, which contain amino groups to which osmic acid can easily adsorb, resulting in electron density under an electron microscope. According to the current literature [21,51,54], degeneration of neuronal cytoplasm and synaptic boutons is characterized by dark electron density under an electron microscope.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the NMJ boutons contained autophagosomes (Fig. 6H-H') [54] and abnormal mitochondria (Fig. 8E, E''), which are associated with synaptic degeneration [13].…”
Section: Discussionmentioning
confidence: 99%